Physiotherapy-Led Multidisciplinary Care for Cardiovascular and Temporomandibular Health: The Role of Laboratory Medicine, Dentists, and Pharmacological Strategies - Alshehri, Abdulrahman Fahran; Alotaibi, Mona Mousa; Al Burayk, Abdullah Ayidh Saud; Alzabadin, Mohammed Ahmed M; AlBishr, Yahya Abdullah; Alanazi, Eman Jamaan; Halawi, Nujud Ali; Sayqal, Muzaynah Munaji Ahmed; Eshaq, Shatha Aziz Abdullah; Alotaibi, Taghreed Miqad (Journal of Posthumanism, 2024)
Cardiovascular diseases (CVDs) and temporomandibular disorders (TMDs) are prevalent and often comorbid conditions that impact systemic and musculoskeletal health. Emerging evidence highlights overlapping inflammatory, neuromuscular, and psychosocial mechanisms, necessitating coordinated interdisciplinary care. This scoping review explores the integration of dentistry, laboratory medicine, and pharmacological strategies within physiotherapy-led multidisciplinary care models targeting patients with both CVD and TMD. Using PRISMA-ScR guidelines, 22 studies were analyzed to map the contributions of each discipline and identify synergistic care strategies. Dentists were central in TMD diagnosis and referral; laboratory diagnostics enhanced cardiovascular risk monitoring; pharmacological therapies supported symptom control and systemic balance; and physiotherapists coordinated rehabilitation and interdisciplinary communication. The findings support the feasibility and value of integrated care models. Recommendations for implementation in Saudi Arabia include guideline development, clinical integration, provider training, and support for policy reform aligned with Vision 2030 healthcare transformation goals.